2015
DOI: 10.5152/anatoljcardiol.2015.6607
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and its effects on cardiovascular diseases: a narrative review

Abstract: Obstructive sleep apnea (OSA) occurs in 5%-14% of adults but is often undiagnosed. Apneas cause acute physiological changes, including alveolar hypoventilation and pulmonary artery vasoconstriction; they also promote chronic vascular disease secondary to increased platelet adhesiveness, endothelial dysfunction, and accelerated atherosclerosis. The Sleep Heart Health Study demonstrated that OSA is a risk factor for stroke and that an increase of 1 unit in the apnea-hypopnea index increases stroke risk by 6% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
0
19
0
2
Order By: Relevance
“…Independent studies have shown that patients with OSAHS are at increased risk of ischemic heart disease, atherosclerotic coronary disease, diabetes, hypertension, congestive heart failure, acute coronary syndrome, stroke, and cardiovascular mortality [6][7][8][9]. Moreover, OSAHS patients have increased frequency of stroke and arterial fibrillation [10]. The application of continuous positive airway pressure to increase air pressure in the throat and prevent its collapse could reverse or attenuate OSA and its associated cardiovascular effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies have shown that patients with OSAHS are at increased risk of ischemic heart disease, atherosclerotic coronary disease, diabetes, hypertension, congestive heart failure, acute coronary syndrome, stroke, and cardiovascular mortality [6][7][8][9]. Moreover, OSAHS patients have increased frequency of stroke and arterial fibrillation [10]. The application of continuous positive airway pressure to increase air pressure in the throat and prevent its collapse could reverse or attenuate OSA and its associated cardiovascular effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a common sleep disorder characterized by repetitive occlusion of upper airway during sleep, generally defined as breathing pause lasting for ≥10 s and the apnea-hypopnea index (AHI) of ≥5 events/h during sleep (Rivas et al 2015). The morbidity of OSA is 5-14% in adults, and higher in older people (Rivas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Divided OSAS patients into groups according to FRS score determined the identification of a low-risk group (with FRS < 10) and non-low-risk group (with FRS ≥ 10) [11]. Recent studies demonstrate that OSA is a common treatable cause of drug-resistant hypertension, risk factor for paroxysmal supraventricular tachycardia and atrial fibrillation, is an independent risk factor for ischemic stroke [15,16]. OSAS comorbidities are not fully identified, but cardiovascular diseases (treatmentresistant hypertension, arrhythmias, myocardial infarction, even sudden death), metabolic diseases (obesity and diabetes), obstructive lung diseases (COPD and asthma), neurological diseases, psychiatric disorders are considered pathological consequences, that can be prevented [17][18][19][20] in order to preserve the social integration and professional activity [8].…”
Section: Resultsmentioning
confidence: 99%